2019
DOI: 10.1002/adem.201900772
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Temperature Compression Deformation Behavior of Commercial Pure Zr Combined with the Constitutive Equation and Processing Map

Abstract: The compression deformation behavior of commercial pure zirconium at elevated temperature is systematically investigated at different conditions. The corresponding deformation mechanism of pure Zr is clarified for analyzed flow stress, work hardening rate, activation energy, and microstructure. A modified Arrhenius‐type equation is proposed for future numerical simulation, which shows a good relativity between the theoretical and experimental data. The apparent deformation activation energy is 209 kJ mol−1, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…The aforementioned investigations indicated that the interrelationships between the parameters are still relatively simple; however, the power dissipation and microstructure evolution under the accumulated deformation are not understood in depth. It is worth noting that the processing map, as a method of visualization to reproduce the dynamic metallurgical processes of metallic materials, has been widely used in the processing of other metals, [ 20–22 ] but it is very unusual in molybdenum processing.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned investigations indicated that the interrelationships between the parameters are still relatively simple; however, the power dissipation and microstructure evolution under the accumulated deformation are not understood in depth. It is worth noting that the processing map, as a method of visualization to reproduce the dynamic metallurgical processes of metallic materials, has been widely used in the processing of other metals, [ 20–22 ] but it is very unusual in molybdenum processing.…”
Section: Introductionmentioning
confidence: 99%